Employment and Earnings of International Science and Engineering Graduates of U.S. Universities: A Comparative Perspective - Campbell, Throy A.; Adamuti-Trache, Maria; Bista, Krishna (Journal of International Students, 2018)
International students represent a large percentage of the student population in science, technology, engineering, and mathematics (STEM) programs at American colleges and universities. Although graduates of these programs are identified as having high employability, productivity, and earnings in the 21st-century job market, there is limited evidence on the effect of citizenship/visa status on these indicators. In this study, we examined the employment status and earnings of international (foreign-born) and American-born graduates of U.S. universities, particularly in science and engineering fields. Based on a sample of 14,400 graduates between 2004 and 2013, of whom 12% were foreign-born, the results indicated that foreign-born graduates (i.e., with temporary status or permanent status) had comparable or better outcomes than American-born graduates in terms of employment and earnings